Helicase lymphoid-specifics and selenoprotein P1 are potential candidate genes in the progression and prognosis of lung adenocarcinoma - Tian, Gang; Lin, Xiang-Xiao; Zhang, Xue-Mei; He, Zhun; Hu, Zhi-Liang (Translational Cancer Research, 2019)
Background: Lung adenocarcinoma (AD) remains one of the most common cancers. Early diagnosis of AD improves therapeutic strategy and lengthens survival time. The objective of this study is to identify hub genes influencing the process of lung AD. Methods: The microarray profiles of GSE43458 were extracted from the Gene Expression Omnibus (GEO) database to screen potential targets during lung AD. Differentially expressed genes (DEGs) between AD patients and normal controls were detected. Then gene ontology (GO) and Kyoto Encyclopedia of Gene and Genome (KEGG) pathway analysis were performed. Moreover, the major modules of protein-protein interaction (PPI) network of those DEGs were performed using the MCODE plug of the Cytoscape. The hub genes were validated in the Oncomine and GEPIA datasets. Additionally, the prognostic values of hub genes were evaluated in Kaplan Meier plotter and GEPIA databases. Results: Totally, 859 DEGs were identified, including 278 up-regulated and 581 down-regulated genes. Functional annotation suggested those DEGs were related to cell adhesion, migration and motility. Besides, helicase lymphoid-specifics (HELLs) and selenoprotein P1 (SEPP1) were regarded as hub genes in AD. Then, the upregulation of HELLs and downregulation of SEPP1 were validated in the Oncomine and GEPIA databases, respectively. Moreover, Kaplan-Meier and GEPIA databases also suggested both HELLs and SEPP1 could affect the prognosis of lung AD patients. Conclusions: Our study demonstrated HELLs and SEPP1 were hub genes contributing to the progress of lung AD. They could be potential target genes for the diagnosis and therapy of lung AD.